Incidence, Morbidity and years Lived With Disability due to Type 2 Diabetes Mellitus in 204 Countries and Territories: Trends From 1990 to 2019 - Zhu, Rongrong; Zhou, Shan; Xia, Liang; Bao, Xiaoming (Frontiers in Endocrinology, 2022)
Background We aimed to examine the descriptive epidemiology and trends in the burden of type 2 diabetes mellitus (T2DM). Methods Data were extracted from the Global Burden of Disease 2019 dataset. Estimated annual percentage changes (EAPCs) were calculated to assess the trends in incidence rate, mortality and disability-adjusted life-years (DALYs) associated with T2DM. Measures were stratified by sex, region, country, age and social development index (SDI) value. Results The global age-standardized incidence rate of T2DM increased from 1990 to 2019, with an EAPC of 1.25 (95% CI, 1.19 to 1.31). In 2019, the highest age-standardized incidence rate of T2DM was observed in high-SDI regions, and the largest increase in this rate from 1990 to 2019 was also in high-SDI regions (EAPC, 1.74;95% CI, 1.57 to 1.90). At the regional level, Central Asia (EAPC, 2.53;95% CI, 2.45 to 2.61) had the largest increase in the age-standardized incidence rate of T2DM from 1990 to 2019. At the national level, Luxembourg (EAPC, 4.51;95% CI, 4.37 to 4.65) and Uzbekistan (EAPC, 3.63; 95% CI, 3.44 to 3.82) had the largest increases in the age-standardized incidence rate of T2DM from 1990 to 2019. The global age-standardized death and DALY rates increased from 1990 to 2019, with EAPCs of 0.26 (95% CI, 0.16 to 0.37) and 0.81 (95% CI, 0.77 to 0.85), respectively. The age-standardized death and DALY rates showed the largest increases in Central Asia, South Asia and Southern Sub-Saharan Africa. Conclusions Globally, the age-standardized incidence, death and DALY rates increased from 1990 to 2019. Central Asia, South Asia and Southern Sub-Saharan Africa were found to have the greatest burden of T2DM. Future strategies should focus on these high-risk regions and other high-risk populations.